Activation of the adenosine A2A receptor attenuates experimental autoimmune encephalomyelitis and is associated with increased intracellular calcium levels. (25th August 2016) - Liu, Yumei; Zou, Haifeng; Zhao, Ping; Sun, Bo; Wang, Jinghua; Kong, Qingfei; Mu, Lili; Zhao, Sihan; Wang, Guangyou; Wang, Dandan; Zhang, Yao; Zhao, Jiaying; et al.
Highlights: The selective A2AR agonist, CGS21680 can inhibit the EAE progression. Treatment with CGS21680 significantly suppressed specific lymphocyte proliferation. Treatment with CGS21680 reduced infiltration of CD4+ T lymphocyte in nerve tissue. Treatment with CGS21680 reduced the expression of inflammatory cytokines. CGS21680 can increase the intracellular calcium concentration in lymphocytes. Abstract: Multiple sclerosis (MS) is a common autoimmune disease that inevitably causes inflammatory nerve demyelination. However, an effective approach to prevent its course is still lacking and urgently needed. Recently, the adenosine A2A receptor (A2AR) has emerged as a novel inflammation regulator. Manipulation of A2AR activity may suppress the MS process and protect against nerve damage. To test this hypothesis, we treated murine experimental autoimmune encephalomyelitis (EAE), a model for MS, with the selective A2AR agonist, CGS21680 (CGS). We evaluated the effects of CGS on the pathological features of EAE progression, including CNS cellular infiltration, inflammatory cytokine expression, lymphocyte proliferation, and cell surface markers. Treatment with CGS significantly suppressed specific lymphocyte proliferation, reduced infiltration of CD4 + T lymphocytes, and attenuated the expression of inflammatory cytokines, which in turn inhibited the EAE progression. For the first time, we demonstrate that CGS can increase the intracellular calcium concentration ([Ca 2+ ] i ) in murine lymphocytes, which may be the mechanism underlying the suppressive effects of CGS-induced A2AR activation on EAE progression. Our findings strongly suggest that A2AR is a potential therapeutic target for MS and provide insight into the mechanism of action of A2AR agonists, which may offer a therapeutic option for this disease.